Ameliorative Effects of Indole Acetic Acid and Naphthalene Acetic Acid on Some Biochemical Parameters of Soybean Exposed to Lead Toxicity - Ailenokhuoria, Bukola Victoria; Olaiya, Charles O (The International Journal of Biotechnology, 2022)
Lead (Pb) is a potential pollutant that readily accumulates in soils. IAA and NAA belongs to plant hormone auxin that promote plants growth. This work aim at examining possible ameliorative effects of Indole acetic acid (IAA) and Naphthalene acetic acid (NAA) on some biochemical parameters of soybean exposed to Pb toxicity. Seeds of soybean (TGX 1835-10E) genotype were sown in 5kg bags of soil containing 1000mg/L of Lead nitrate (PbNO3). 40mg/L, 80 mg/L and 120mg/L each of IAA and NAA were prepared and applied by foliar method after 5 weeks of planting. Photosynthetic pigments, mineral elements and antioxidant enzymes were determined on the root, stem and leaf after 7 weeks of planting. Data were analysed using anova at 5% level of significance. The results showed that the level of chlorophyll a, b and carotenoid, mineral elements and antioxidant enzymes significantly increased in the root, stem and leaf of soybean treated with different concentration of Indole acetic acid (IAA) and Naphthalene acetic acid (NAA) as compared with the control (C+ve). All bioregulators (IAA and NAA) concentrations significantly decreased in the level of Pb2+ (except 40mg/L IAA in the root and leaf while all concentration have significant effects in the stem) and also all concentration of (IAA and NAA) significantly increased in the level of biochemical parameters to different extent as compared to control(C+ve). These results show that Indole acetic acid (IAA) and Naphthalene acetic acid (NAA) could ameliorate the Pb toxicity and therefore will be of relevance to agricultural producers.